"Ten Days a ’Grass Widow’ - Forty-eight Hours a Wife": Sexual Division of Labour in Trawlermen’s Households - Binkley, Marian; Thiessen, Victor (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1988)
A strict dichotomy of gender and work roles has long characterized the offshore trawler fishery. Men’s constantly varying work period, about ten days sea time to every forty-eight hours ashore, forces wives to become reluctant matriarchs, a role they must drop when their husbands land. Incongruity of expectations and behaviour is thus built in. Successful adjustment to sea-time roles by both is often dysfunctional to family stability, and to the health and recreation of the labour force. Women’s double-role strategies are described using ethnographic and interview data. These strategies vary with the historically changing structures of the industry, kinship and community; with their stage in the life cycle; with the expectations of husband and wife; and with the constraints imposed by vessel schedules and company policies.